Adaptasi Komunikasi Mahasiswa Perantau: Studi Pada Ippm Semaku Di Universitas Negeri Padang - Alpian Syah Nafira; Sri Dwi Fajarini (STAI Bumi Silampari, 2025)
This study analyzes the communication adaptation of Semaku migrant students (Seluma, Manna, and Kaur) at Padang State University using Young Yun Kim's Intercultural Communication Adaptation Theory. Using qualitative methods, informants were a group of 15 Semaku IPPM students consisting of 10 migrant students and 5 local students. Data collection techniques included in-depth interviews, non-participatory observation, and documentation. The results of the study indicate that adaptation occurs through a stress-adaptation-growth cycle in three dimensions. 1. Personal communication: Minangkabau linguistic barriers are the main adaptation challenges overcome through code-switching and code-mixing strategies. 2. Social communication: Semaku IPPM functions as a psychological buffer and cultural bridge that facilitates the formation of hybrid identities, but has the potential to trigger ethnic enclosure. 3. Mass communication: digital media becomes an arena for identity negotiation through bilingual captions that expand intercultural interactions. Psychological transformation takes place from social anxiety to resilience until students are able to act as cultural mediators. This study validates Kim's theory in the Indonesian context and recommends inclusive orientation programs, balancing regional organizational support with cross-regional participation, and optimizing digital platforms to support communication adaptation of migrant students.